Pulse width modulated capacitor for series compensation. - Lopes, L.A.C.
This paper presents a variable reactance type series compensator with pulse-width modulation (PWM) capability. On a per-phase basis, it can be represented by a bidirectional force-commutated switch in parallel with a combination of a capacitor in series with another bidirectional force-commutated switch. The equivalent reactance of the capacitor circuit can be continuously varied, with no risk of short-circuiting the capacitor or interrupting the line current. A simple and reliable PWM AC controller which requires only four force-commutated switches and a three-phase diode bridge is proposed for the implementation of the three-phase compensator. The degree of series compensation is controlled by duty cycle variation of a common train of pulses. No low order harmonics are generated since the force-commutated switches can operate at frequencies higher than that of the AC mains. The operating principles are presented and the theoretical analysis is verified by digital simulation and experimental results on a laboratory set-up
Keywords: AC-AC power converters; FACTS; PWM; PWM AC controller; Bidirectional force-commutated switch; Capacitor; Capacitor circuit; Digital simulation; Duty cycle variation; Equivalent reactance; Line current interruption; Pulse width modulated capacitor; Pulse-width modulation; Reactive power control; Series compensation; Short-circuiting.; Three-phase compensator; Three-phase diode bridge; Variable reactance type series compensator